Some considerations about the absence of moral sensitivity and the learning process of students who practice bullying - Brasão , Maria Carolina Ribeiro; Assis , Orly Zucatto Mantovani de (Seven Editora, 2023)
This article aims to make some reflections about the cognitive and moral development that develops in the context of bullying in Brazilian schools. And yet, to highlight the pertinence about the understanding about these concepts before the pedagogical doing. This text is the result of a study and analysis of the doctoral thesis that was discussed at the School of Education – Unicamp in 2016. In the State schools investigated, this type of violent action that brings physical and psychological damage to those involved can demonstrate the absence of moral sensitivity of those who practice it and denote some gaps present in the process of construction of elementary logical structures of thought. We observed the need to intervene pedagogically in order to minimize this type of conflict that is affected among students. Among these attempts, we highlight the practice of dialogue within schools to be developed among all members who participate in it, and also consider the need to know how these boys and girls build their cognitive structures and develop morally. That is, it is necessary that as educators we approach the process of construction of cognitive competencies that need to be constantly discussed in school curricula as well as socio-emotional competencies that are often not considered in the daily life of the classroom, since the focus of the pedagogical work is to account for the contents inherent to the curricular disciplines. It was through this research that we sought to produce knowledge that could be used by teachers and other specialists about the need to get to know better those students who are often involved with bullying situations (in particular, as perpetrators), who bring in the midst of their relationships striking characteristics of the psychological subject in development. In this work, we were able to investigate the relationship between the level of cognitive development of the perpetrators of bullying and the fact that they present difficulties in the learning process in specific disciplines of the curriculum, especially in mathematics, which consists of the acquisition of logical mathematical knowledge, and lack of moral sensitivity. The following instruments were used to carry out the present study: Piagetian tests for the diagnosis of operative behavior; questionnaire to obtain demographic data and final concepts of students with a profile of bullying authors in the disciplines of mathematics and Portuguese Language. We were able to verify that the gaps in the level of cognitive development, as well as the low quality in the interpersonal relationships of students who are often involved in bullying actions, signaled by the absence of moral sensitivity, can affect learning and consequently bring limitations to the development and construction of certain curricular skills. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-120